Designing a Comprehensive Internet Banking Website Usability Model - Azad Shaibani; Masoud Keimasi; Rosa Hendijani; Mohammadsaleh Torkestani (مطالعات مدیریت کسب و کار هوشمند, 2021)
Nowadays Due to the increasing advances in technology in the banking industry and changes in the expectations of bank customers, especially the desire to eliminate unnecessary face-to-face Services and the need to receive 24-hour banking services, virtual portals, especially Internet banking websites have been welcomed. According to many experts success of websites is closely related to their degree of usability, so ease of use can act as a powerful leverage to attract customers to a bank that has a more usable website. In this study, after a comprehensive review of the literature, interviews with 41 experts in this field and then by a qualitative method of theme analysis, a comprehensive model of internet banking website was presented. In this model, usability is affected by two groups of external dimensions and internal dimensions, which in case of compatibility with users' expectations, the website is evaluated as usable and as a result, user satisfaction is achieved. Due to the wide range of customers of commercial banks, in addition to traditional segmentation, it is recommended that intelligent segmentation of target users done to improve the usability of Internet banking websites.